PERUBAHAN KUALITAS BUBUK PEWARNA ALAMI BUAH BUNI (Antidesma Bunius (L) SPRENG) SELAMA PENYIMPANAN DENGAN MENGGUNAKAN METODE AKSELERASI - Niken Ayu Permatasari; Yusma Kurnia Deofsila (Jurnal Teknologi Industri Pertanian, 2021)
Chinese laurel fruit (Antidesma bunius (L) Spreng) can be used as a natural dye due to anthocyanin content which produces red colour at a low pH (1-3). This study aimed to determine changes in the quality of the natural dyes powder from chinese laurel fruit (Antidesma bunius (L) Spreng) during storage time by using accelerated method. Production of chinese laurel fruit extracts was done with distilled water + 3% citric acid with a ratio of 1:3 and the addition of maltodextrin as much as 15%. Natural dyes powder from chinese laurel fruit packaged with PP plastic and stored at temperatures 28°C, 35°C and 55°C to observe the changes of total anthocyanin and its colour during storage. Changes in the quality of the natural dyes powder laurel fruit during storage were due to the presence of pigments from anthocyanins which are degraded by heat. So that the total anthocyanin and the color of te natural coloring powder of laurel fruit decreased. Characteristics of analysis of natural dyes powder at the beginning of storage time (H0) showed moisture content of 2.53%, total anthocyanin of 56.24 mg anthocyanin/100 g dye powder, vitamin of C 12.54 mg anthocyanin/ 100 g dye powder, water solubility of 73.90%, total titrated acid of 8.04%, and red colour. Dye powder stored in 28°C showed less quality decreasing and longer shelf life compared to that stored in temperature 35°C and 55°C . The shelf life of natural dyes product from chinese laurel fruit that stored in 28°C, 35°C, and 55°C were 241 days, 101 days, and 14 days, respectively. Keywords: antidesma bunius (L) Spreng, anthocyanin, chinese laurel fruit, natural dye powder, accelerated method